The innovative mindset : 5 behaviors for accelerating breakthroughs - Sweeney, John, 1965- (Wiley, 2016)
"Behavioral Innovation demystifies the question of "What does it take to be more innovative?" by introducing the idea that innovation is much more of a behavior than a theory or corporate-defined initiative. Like any other behavioral change (losing weight, getting stronger, playing the piano, becoming a better partner), we can identify what we need to need to practice in the area of innovation to create a sustainable regimen that allows us to transform how we act, and most, importantly, reap the positive benefits from our behaviors. The book will include poignant, current case studies that show the reader how living in the Mindset of Discovery and practicing the Big Five can and will lead to significant business productivity and profitability"--